THE Psychomotor evaluation in preschools children from 4 to 6 years old: a physiotherapeutic view - Ribeiro, Karoline (2022)
At the beginning of the children's school period, psychomotricity is one of the most important issues to be addressed, mainly because of its influence on difficulties in the learning process. The psychomotor elements help from the ability to express oneself through movements to issues related to human motor development. The physical therapist has the ability to evaluate the evolutionary process of motor development, to guide and intervene when the individual presents abnormalities in this process, in order to promote adequate and harmonious motor experiences. The present study aimed to verify whether psychomotricity influences motor development in pre-school children aged 4 to 6 years old, in two public schools in São Miguel do Oeste – SC, using the Motor Development Scale (MDS), under a physiotherapeutic viewpoint, with the performance of sessions for the individuals who showed motor deficits and evaluation of progress. This is a quantitative, experimental study of the non-controlled clinical trial type, in which 10 preschool children were evaluated, and 3 of these presented motor deficits – being invited to participate in 10 physiotherapeutic sessions. In the comparison made between the pre and post intervention evaluations, it was observed, through the analysis of percentage variance, that all the individuals presented progress above 20% in the items of fine motor skills, balance, and temporal organization, according to the specific motor age (MA) and motor quotient (MQ) variables. Thus, we conclude that physiotherapy, together with educators, can contribute to the improvement of psychomotricity, exerting a positive influence on the motor development of preschool children aged 4 to 6 years.